An Investigation of Indoor Air Quality in a Recently Refurbished Educational Building - McLeod, R. S.; Mathew, M.; Salman, D.; Thomas, C. L. P. (Frontiers in Built Environment, 2022)
Young people spend extended periods of time in educational buildings, yet relatively little is known about the air quality in such spaces, or the long-term risks which contaminant exposure places on their health and development. Although standards exist in many countries in relation to indoor air quality in educational buildings, they are rarely subject to detailed post occupancy evaluation. In this study a novel indoor air quality testing methodology is proposed and demonstrated in the context of assessing the post-occupancy performance of a recently refurbished architecture studio building at Loughborough University, UK. The approach used provides a monitoring process that was designed to evaluate air quality in accordance with UK national guidelines (Building Bulletin 101) and international (WELL Building) standards. Additional, scenario-based, testing was incorporated to isolate the presence and source of harmful volatile organic compounds, which were measured using diffusive sampling methods involving analysis by thermal desorption - gas chromatography - mass spectrometry techniques. The findings show that whilst the case-study building appears to perform well in respect to existing national and international standards, these guidelines only assess average CO2 concentrations and total volatile organic compound limits. The results indicate that existing standards, designed to protect the health and wellbeing of students, are likely to be masking potentially serious indoor air quality problems. The presence of numerous harmful VOCs found in this study indicates that an urgent revaluation of educational building procurement and air quality monitoring guidelines is needed.